Color Image Encryption Using LFSR, DNA, and 3D Chaotic Maps - Allawi, Salah Taha; Alshibani, Dina Riadh (International Journal of Electrical and Computer Engineering Systems, 2022)
One of the most important challenges facing researchers is to find new methods to protect data sent over the Internet and prevent unauthorized access to it. In this paper, we present a new method for encrypting image data divided into two stages. The first stage requires redistributing the positions of the pixels by using a key of random numbers generated by linear feedback shift registers and then encrypting the data using deoxyribonucleic acid rules. The data generated in the previous stage is encrypted again using chaotic maps to increase the level of security in the second stage. Several statistical tests were implemented to verify the efficiency of the proposed method and compare the results with the work of other researchers. The results of the tests proved a reasonable safety rate compared to other techniques.